Protected Areas in Europe – Challenges for Scientific Collaboration. Experiences of the Research Group NeReGro - Mose, Ingo; Hammer, Thomas; Siegrist, Dominik; Weixlbaumer, Norbert (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
This paper addresses development and experiences of an international group of researchers with a focus on area protection in Europe. Under the acronym "NeReGro" (for "New regional development and large protected areas") four university research groups in geography from Switzerland, Austria and Germany practice successfully a rather lose, informal way of collaboration for almost20 years. Core subject of their joint activities is the considerable change experienced in area protection in Europe for quite some time. This is especially mirrored by large protected areas, many of which carry out a multitude of functions beyond the classical tasks of nature conservation. A considerable part of this research appears relatively isolated though, relatively disconnected and with limited mutual recognition. The development of NeReGro well illustrates the benefits that can be generated instead from ways of systematic collaboration for research on protected areas at large. These regard the development of a comparative international research agenda, the recognition of the societal implications of area protection, and the enhancement of the local-regional research perspective by a global view. Besides the added value of collaboration visibale through the work of NeReGro, the case of the research group equally illustrates limits of collabation similarly characteristic for protected areas research in Europe at large. Against this background, the consistent development of appropriate forms of research collaboration at European scale are demanded in order to meet future challenges caused by planning and management of protected areas.